AXIOLOGICAL ASPECTS OF ADULT EDUCATION IN FRANCE - Batechko, Nina; Durdas, Alla (Educological discourse, 2018)
The article substantiates the axiological aspects of adult education in France. The peculiarities of adult education as an integral and, at the same time, a separate part of the French education system are analysed in the context of the trends of the modern European educational space. Forms and methods of organizing adult education in France have been presented, taking into account the adaptation of specialists to transient changes and possible risks in employment. The axiological aspects of adult education have been revealed as important factors in harmonizing the universal and professional values of a specialist, formation of an individual system of value orientations of an adult. The value orientations of adult education have been singled out taking into account the socioeconomic and spiritual development of the French community. It is pointed to the importance of scientific comprehension and generalization of the multifaceted French experience in the field of adult education for the purpose of its realization and the value direction of the functioning of education during life in Ukraine.